Factors that Correlation to Occupational Contact Dermatitis Among Tobacco Farmers in Jember District, East Java Province, Indonesia - Anita Dewi Prahastuti Sujoso1,2, Tri Martiana*3 , Santi Martini4 ,Firman Suryadi Rahman1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction. Contact dermatitis is positived by most agricultural sector workers. Tobacco farming is one of the places where chemicals are sourced from pesticides, fertilizers, and also nicotine derived from tobacco leaves. This study aims to analyze the factors associated with contact dermatitis in tobacco farmers in Jember, East Java Province, Indonesia. Method. The research design is case control with 155 tobacco farmers. The dependent variable of this study is Occuptional Contact Dermatitis (OCD) as measured through the results of a doctor’s examination. Independent variables are individual factors and occupational factors. Individual factors include age, sex, education, individual hygiene, use of personal protective equipment, and complaints of GTS. Occupational factors consist of the main job, additional work, types of tobacco leaves, work at risk, work period, length of work, length of rest. Data analysis used Chi-Square test with a significance value of p <0,05. Result and Discussion. The results revealed that factors related to OCD in tobacco farmers in Jember Regency were age (p = 0.037), education (0,013), GTS complaints (p = 0,030), type of tobacco leaf (p=0,005), working periode (p=0,042) and working hours (p=0,008). Conclusion Individual factors related to OCD in tobacco farmers are age, education, and GTS complaints. Occupational factors related to OCD are the type of tobacco leaves, working periode and length of work. This study revealed that OCD through promotion and integrated occupational health education.